Poverty and Social Impact Analysis by the IMF : Review of Methodology and Selected Evidence - Gillingham, Robert (International Monetary Fund, 2008)
The Poverty Reduction and Growth Facility (PRGF) is used by the IMF to provide support for countries' implementation of their poverty reduction and growth strategies. A key requirement in the design of PRGF programs is understanding the effects of reform program measures on vulnerable groups-particularly the poor-and how to devise measures to mitigate any negative effects. Poverty and social impact analysis (PSIA) is a critical instrument for pursuing this goal. The IMF has therefore established a small group of staff economists to facilitate the integration of PSIA into PRGF-supported programs. In this book, the group's members review analytical techniques used in PSIA as well as several important topics to which PSIA can make valuable contributions. These reviews should prove useful and interesting to readers interested in PSIA in general and the IMF's PSIA efforts in particular.